Pendampingan Penghitungan dan Pelaporan PPH 21 Masa Melalui E-SPT dan DJP Online Bagi Siswa Siswi SMK Dharma Widya Tangerang - Melatnebar, Benyamin; Laluur, Eugenius (RUBINSTEIN, 2022)
This research project in the form of community service aims to provide training and education on how to calculate, pay and report Income Tax (PPh) article 21 for employees through the E-SPT application and DJP Online to class X, XI students of SMK Dharma Widya so that training participants gain knowledge to enter the world of work in accordance with the field of science studied. This training can also increase understanding and deepen the practice of calculating, paying and reporting PPh 21 employees through E-SPT and DJP Online. The method used in this training activity is descriptive analysis, namely identifying the types of PPh 21 items and making worksheets to facilitate calculations considering the pandemic conditions are not yet conducive, this training activity uses offline training methods but pays attention to health protocols and the implementation of training that runs in accordance with which are desired. This training is carried out for 1 (one) day. The training participants were 60 people from Dharma Widya Vocational School. The material provided to the training participants includes general income tax concepts, understanding, subjects, objects, income tax rates, the practice of calculating income tax for 21 employees with fixed income. Based on the assessment carried out, the results of the training activities can provide insight, improve the ability of training participants in the accounting field, make payments and report PPh 21 employees according to tax laws, so that they are ready to work as employees in the financial sector.